The State of Health Information Systems Research in Africa: A Scoping Review - (:unkn) unknown (My University, 2022)
Research on health information systems is gaining momentum, given the importance of the topic in curbing various healthcare issues which are challenging the African health system. The relevance of the topic is reflected in the exponential growth of technological innovations for health and scientific research that assesses their impact. This plethora of research avenues poses a situation of missing evidence on the state of the art of the topic in its diversity. In this research, we report on an overview of research on health information systems across Africa, outlining key insights such as current trends and institutions addressing the topic. We examined 353 articles collected in the Scopus database, and screened them using the biblioshiny. Based on the findings, we ascertained the intricacy of the topic and pinpointed key areas for future research. The outcomes of our research provide information for practitioners engaged in understanding the advancement and state of the art of technology for healthcare in Africa, and research analysis for scholars and researchers on health technologies in Africa.
Keywords: African Research